2015
DOI: 10.1186/s13287-015-0249-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of metformin at low concentration on epithelial–mesenchymal transition of CD44+CD117+ ovarian cancer stem cells

Abstract: BackgroundAlthough metformin, a first-line drug for treating diabetes, may play an important role in inhibition of epithelial ovarian cancer cell growth and cancer stem cells (CSCs), metformin at low dose showed less effect on the proliferation of ovarian cancer cells. In this study, we evaluated the effect of metformin at low dose on ovarian CSCs in order to understand the molecular mechanisms underlying.MethodsThe inhibitory effects of metformin at los dose on proliferation and population of ovarian cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 38 publications
7
54
0
2
Order By: Relevance
“…However, in our in vitro model we observed no change in proliferation or cell cycle in the presence of platelets. Furthermore, we previously reported that micromolar metformin did not alter the proliferation of SKOV3 or A2780 ovarian cancer cells, which was reaffirmed by Zhang and colleagues [21, 57]. Herein, we confirm that micromolar concentrations of metformin have no effect in SKOV3 cell proliferation and report that this is also true for UCI101 cells.…”
Section: Discussionsupporting
confidence: 89%
“…However, in our in vitro model we observed no change in proliferation or cell cycle in the presence of platelets. Furthermore, we previously reported that micromolar metformin did not alter the proliferation of SKOV3 or A2780 ovarian cancer cells, which was reaffirmed by Zhang and colleagues [21, 57]. Herein, we confirm that micromolar concentrations of metformin have no effect in SKOV3 cell proliferation and report that this is also true for UCI101 cells.…”
Section: Discussionsupporting
confidence: 89%
“…Metformin had been shown to act as an inhibitor of proliferation by activating AMPK and consequently inactivating the mammalian target of rapamycin (mTOR)-related signaling pathway, which was considered one of the potential key mechanisms mediating the anti-tumor activity of metformin 31. Furthermore, metformin had been found to reduce ovarian cancer stem cells population,32 induce cell cycle arrest,33 and increase protein acetylation to alter patterns of gene expression34 by some in vitro and in vivo analyses. Recently, metformin was reported to have the potential to improve antitumor T cell immunity by dampening CD39/CD73-dependent myeloid-derived suppressor cells suppressive activity in ovarian cancer patients 20…”
Section: Discussionmentioning
confidence: 99%
“…This speculation can be partly supported by a previous study that demonstrated that CD117 enhanced the tumorigenicity of EOC cells by conferring a CSC phenotype 29. Additionally, other mechanistic investigations have revealed that CD117 might contribute to EOC development by inducing epithelial–mesenchymal transition, a well-established molecular event that is involved in cell invasion and metastasis 30,31. Chene et al recently even have detected high expression of CD117 in the premalignant lesions of EOC, suggesting its potential role as a diagnostic marker for early ovarian tumorigenesis 32.…”
Section: Discussionmentioning
confidence: 77%